The Effect of Sensory Marketing and Audio Branding on Repurchase Intention Mediated by Brand Experience - Skolastika, Flavian; Daud, Ilzar; Afifah, Nur; Juniawati (Yayasan Sinergi Kawula Muda, 2025)
This study explores the influence of Sensory Marketing and Audio Branding on purchase intention among consumers of Diantara Kopi, a popular coffee shop in Pontianak, Kalimantan Barat. Sensory Marketing, which engages multiple consumer senses, plays a crucial role in shaping perceptions and purchasing behavior, while Audio Branding leverages sound to create a distinct brand identity. Using a quantitative approach, data were collected through surveys from 236 Diantara Kopi customers and analyzed using structural equation modeling (SEM). The results highlight the importance of sensory-driven branding strategies, demonstrating that a well-crafted sensory and audio experience can significantly boost consumer satisfaction and encourage repeat visits. The study provides valuable insights for businesses fostering customer loyalty through effective sensory and audio branding techniques.